Bukhta Akhomtenʺ s bukhtoi︠u︡ Tikhirka po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana 1919 g. / Sʺemka i chertilʺ Kapitana mal. pl. V. Gragaĭtisʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : [Морское министерство, Главное гидрографическое управленіе], 1919)
Relief shown by form lines and spot heights. Depth shown by soundings.; Coordinates for Akhomten Bay given on map: 52°23'56.0"N 158°24'39.0"E.; Title translation: Akhomten Bay with Tikhirka Bay, according to the survey of the Hydrographic Expedition of the Eastern Ocean 1919.; Greenwich meridian.; "No. 402" -- top right margin Grayscale; 1:21,000